2001
DOI: 10.1128/mcb.21.17.5806-5814.2001
|View full text |Cite
|
Sign up to set email alerts
|

Overlapping Functions of the pRb Family in the Regulation of rRNA Synthesis

Abstract: The "pocket" proteins pRb, p107, and p130 are a family of negative growth regulators. Previous studies have demonstrated that overexpression of pRb can repress transcription by RNA polymerase (Pol) I. To assess whether pRb performs this role under physiological conditions, we have examined pre-rRNA levels in cells from mice lacking either pRb alone or combinations of the three pocket proteins. Pol I transcription was unaffected in pRb-knockout fibroblasts, but specific disruption of the entire pRb family dereg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(50 citation statements)
references
References 52 publications
1
49
0
Order By: Relevance
“…Similarly, the hypertrophic growth of rat cardiac myocytes can be blocked by specifically preventing a 37% increase in rRNA synthesis (Brandenburger et al, 2001). The magnitude of these changes compares closely with the B40% suppression of rRNA synthesis exerted by endogenous RB and its relative p130 in embryonic fibroblasts, as determined with knockout mice (Ciarmatori et al, 2001). A similar genetic analysis found that endogenous RB suppresses tRNA levels by 2.4-fold in serum-starved mouse embryonic fibroblasts .…”
Section: Pols I and Iii May Help Mediate The Growth Control Functionsmentioning
confidence: 53%
See 1 more Smart Citation
“…Similarly, the hypertrophic growth of rat cardiac myocytes can be blocked by specifically preventing a 37% increase in rRNA synthesis (Brandenburger et al, 2001). The magnitude of these changes compares closely with the B40% suppression of rRNA synthesis exerted by endogenous RB and its relative p130 in embryonic fibroblasts, as determined with knockout mice (Ciarmatori et al, 2001). A similar genetic analysis found that endogenous RB suppresses tRNA levels by 2.4-fold in serum-starved mouse embryonic fibroblasts .…”
Section: Pols I and Iii May Help Mediate The Growth Control Functionsmentioning
confidence: 53%
“…Note: p53 does not interact with assembled TFIIIB and so is not detected at the pol III promoters it regulates (Crighton et al, 2003) tions). The pol I machinery is also targeted by RB and p53, both of which can reduce its output (Cavanaugh et al, 1995;Voit et al, 1997;Hannan et al, 2000a,b;Pelletier et al, 2000;Zhai and Comai, 2000;Ciarmatori et al, 2001;Sugimoto et al, 2003). It therefore appears that pols I and III are both enmeshed in a network of regulatory interactions that help to coordinate their outputs and promote balanced production of ribosomal components.…”
Section: Coordinate Regulation Of Pols I and Iiimentioning
confidence: 99%
“…All these kinases have been found overexpressed in many cancers. Several tumor suppressors have also been shown to directly interact with UBF: pRb or p130 inhibit in that way subsequent recruitment of cofactors required for rRNA transcription (Cavanaugh et al, 1995;Voit et al, 1997;Hannan et al, 2000a, b;Ciarmatori et al, 2001). p53 also interferes with Pol I activity by destabilizing the SL1-UBF complex required for transcriptional initiation on the rRNA promoter (Zhai and Comai, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…This family of tumor suppressor genes is mutated in many types of cancers and is important in regulation of rRNA synthesis (Ruggero and Pandolfi, 2003). Several studies show a close relationship between Rb and transcription of the rDNA by RNA polymerase I (Cavanaugh et al, 1995;Hannan et al, 2000;Ciarmatori et al, 2001), and deleting Rb leads to increases in rRNA synthesis (Ciarmatori et al, 2001). Thus Whi5 and Rb have roles in both ribosome biogenesis and Start, although the regulatory connections may differ.…”
Section: K a Bernstein Et Almentioning
confidence: 99%